Hepatic Branch Vagotomy Modulates the Gut-Liver-Brain Axis in Murine Cirrhosis - Zhang, Yuan; Kang, Jason D.; Zhao, Derrick; Ghosh, Siddartha S.; Wang, Yanyan; Tai, Yunling; Gonzalez-Maeso, Javier; Sikaroodi, Masoumeh; Gillevet, Patrick M.; Lippman, H. Robert; Hylemon, Phillip B.; Zhou, Huiping; et al. (Frontiers in Physiology, 2021)
Cirrhosis and hepatic encephalopathy (HE) are linked with an altered gut-liver-brain axis, however the relative contribution of hepatic vagal innervation is unclear. We aimed to determine the impact of hepatic vagotomy on the gut microbiome, brain and liver in murine cirrhosis. Methods: 10-15-week-old male C57BL/6 mice with and without hepatic vagotomy underwent carbon tetrachloride (CCl4) gavage for 8 weeks. Frontal cortex [inflammation, glial/microglial activation, BDNF (brain-derived neurotrophic factor)], liver [histology including inflammation and steatosis, fatty acid synthesis (sterol-responsive binding protein-1) SREBP-1, insulin-induced gene-2( Insig2) and BDNF], and colonic mucosal microbiota (16srRNA microbial sequencing) were evaluated on sacrifice. Conventional mice with and without cirrhosis were compared to vagotomized counterparts Results: Conventional control vs cirrhosis: Cirrhosis resulted in dysbiosis, hepatic/neuro-inflammation with glial/microglial activation and low brain BDNF versus controls. Conventional control vs vagotomy controls: Vagotomized control mice had a lower colonic dysbiosis that conventional mice but the rest of hepatic/brain parameters were similar. Conventional cirrhosis vs vagotomized cirrhosis: After vagotomy+cirrhosis, we found lower dysbiosis but continuing neuro-inflammation in the absence of glial/microglial activation versus conventional cirrhosis. Vagotomy+Cirrhosis groups showed higher hepatic steatosis due to higher SREBP1 and low Insig2 protein and altered activation of key genes involved in hepatic lipid metabolism and inflammation. BDNF levels in brain were higher but low in liver in vagotomy+cirrhosis, likely a protective mechanism. Conclusions: Hepatic vagal innervation affects gut microbial composition, hepatic inflammation and steatosis and cortical inflammation and BDNF expression and could be a critical modulator of the gut-liver-brain axis with consequences for HE development.